2017
DOI: 10.1590/0103-8478cr20170036
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal activity of succinic acid isolated from sisal waste (Agave sisalana) against gastrointestinal nematodes of goats

Abstract: This study was conducted to evaluate the in vitro anthelmintic activity of the succinic acid (SA) isolated from sisal waste against gastrointestinal nematodes of goats, using the egg hatching and larvae motility assays. In addition, potential cytotoxicity of SA on Vero cell cultures was investigated by means of MTT (3-4,5-dimethylthiazol-2-yl, 2,5diphenyltetrazolium bromide) test. The SA induced a significant inhibition of egg hatching (P<0.05) at all concentrations tested (60 to 250µg mL-1), and the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…With respect to azelaic acid specifically, identified its possible effect on Caenorhabditis elegans [ 82 ], which was suggested to be associated with the activity of the steroid enzyme 5 alpha-reductase [ 83 ]. Other authors have reported AA against nematodes such as Meloidogyne incognita [ 84 ], Oesophagostomum dentatum [ 85 ], Haemonchus spp., Oesophagostomum spp., and Trichostrongylus [ 86 ]. Moreover, it can be observed a combined effect of fatty acids and tannins on larvae of Toxocora canis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to azelaic acid specifically, identified its possible effect on Caenorhabditis elegans [ 82 ], which was suggested to be associated with the activity of the steroid enzyme 5 alpha-reductase [ 83 ]. Other authors have reported AA against nematodes such as Meloidogyne incognita [ 84 ], Oesophagostomum dentatum [ 85 ], Haemonchus spp., Oesophagostomum spp., and Trichostrongylus [ 86 ]. Moreover, it can be observed a combined effect of fatty acids and tannins on larvae of Toxocora canis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menurut (Santos et al, 2017) limbah dekortikasi sisal mempunyai efek anthelmintik (obat cacing) dalam usus karena mengandung asam suksinat. Pada percobaan secara in vivo, asam suksinat yang diisolasi dari limbah dekortikasi sisal dapat melawan nematoda pada saluran pencernaan domba.…”
Section: Bahan Obatunclassified